Assessment of Nutritional Status of Adolescents: Field Experience from Rural Gujarat, India - Trivedi, Poonam K; Saxena, Deepak; Puwar, Tapasvi; Yasobant, Sandul; Savaliya, Shital; Fancy, Manish (National Journal of Community Medicine, 2016)
Background: Worldwide there are more than 1.2 billion adolescent; more than half of all adolescents live in Asia and India has the highest adolescent population than any other country. Adolescents face a range of health challenges; contributing to increased morbidity and mortality. However, the comprehensive data on status of morbidity are scarce. Present study assesses nutritional status of adolescents attended Adolescent Health Day (AHD) in one of the taluka of Gujarat. Methods: Present study documented nutritional status of adolescents attended 16 AHD organized by health department in Talod block of Sabarkantha district. Screening of adolescents was done for Body Mass Index (BMI) and Hemoglobin estimation. Results: Out of total 821 adolescents, 690 (84%) school-going and 131 (16%) non-school-going adolescents screened, 17% were severely thin and only about half had normal BMI. Less than a percent were overweight. Prevalence of anemia was 6% in girls and 3% in boys. Conclusions: Present study documents poor nutritional status of adolescents in rural Gujarat; narrates an urgent need for better nutrition to combat the problem of undernutrition amongst adolescents. Present study also reinforces a need for further research and documentation of nutritional status of Adolescents to enhance current interventions in the field of adolescent health.